Two new species of the crab spider genus Talaus (Araneae: Thomisidae) from Yunnan Province, China - Tang, Guo; Yin, Chang-Min; Ubick, Darrell; Peng, Xian-Jin (Zootaxa, 2008)
This paper describes 2 new species of the crab spider genus Talaus (Thomisidae: Thomisinae, Talaini) from the Gaoligong Mountains, Yunnan Province, China: T. dulongjiang sp. nov. and T. niger sp. nov. Detailed morphological characters, photos and illustrations of copulatory organs, and a distribution map for the species are presented.